Mind, Body, and Metaphor in Ancient Greek Concepts of Emotion - Douglas Cairns (L'Atelier du CRH)
This paper presents examples of the role played by metaphor in the formation of ancient Greek emotional concepts. Previous studies of emotion in ancient Greek societies have focused chiefly on the terms that the ancient Greeks used to label their emotional experiences. Such an approach is fundamental, yet overlooks important elements of the language of emotion. The characteristic symptoms, physiological changes, expressions, and behaviours associated with the emotions typically become metonyms for the emotions themselves and are represented in cognitive metaphors that form part of a culture’s conceptual model of emotion. Thus the embodied nature of emotions is reflected in language, and in so far as the metaphors and metonyms of folk physiology are limited by the observed phenomena of real physiology and predicated on basic conceptual structures that are rooted in human beings’ embodied nature, no serious study of emotion language can afford to ignore these aspects. A comprehensive study of emotional metaphor in ancient Greek can thus be expected to present much that is, in broad terms, familiar to us from our own languages. The interesting questions, however, concern the interplay between what is universal and what is specific in both the formation and the application of such concepts. This paper explores some of these questions with particular reference to two Greek images: the symptom of shivering or shuddering; and the representation of grief and other emotions as enveloping garments.